Q. 275.0( 1 Vote )

# In each of the question, show that the given differential equation is homogeneous and solve each of them.

(x^{2} + xy)dy = (x^{2} + y^{2})dx **[CBSE 2013]**

**[CBSE 2013]**

Answer :

Here, putting x = kx and y = ky

= k^{0}.f(x,y)

Therefore, the given differential equation is homogeneous.

(x^{2} + xy)dy = (x^{2} + y^{2})dx

To solve it we make the substitution.

y = vx

Differentiating eq. with respect to x, we get

Integrating on both side,

- v - 2log|1 - v| = log|x| + logc

The required solution of the differential equation.

Rate this question :

Solve the following differential equation:

RD Sharma - Volume 2

tan^{-1}x + tan^{-1} y = c is the general solution of the differential equation:

The number of solutions of when y(1) = 2 is:

Mathematics - ExemplarFind the particular solution of the differential equation

given that when

Mathematics - Board PapersSolve the following differential equation:

dy + (x + 1)(y + 1) dx = 0

RD Sharma - Volume 2Find the particular solution of the following differential equation:

when x = 1

Mathematics - Board Papers